2009
DOI: 10.1080/10673220902891836
|View full text |Cite
|
Sign up to set email alerts
|

Update on Research and Treatment of Premenstrual Dysphoric Disorder

Abstract: Many women in their reproductive years experience some mood, behavioral. or physical symptoms in the week prior to menses. Variability exists in the level of symptom burden in that some women experience mild symptoms, whereas a small minority experience severe and debilitating symptoms. For an estimated 5%–8% of premenopausal women, work or social functioning are affected by severe premenstrual syndrome. Many women in this group meet diagnostic criteria for premenstrual dysphoric disorder (PMDD). Among women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
48

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 282 publications
(305 reference statements)
4
114
0
48
Order By: Relevance
“…The neurobiological factors involved in the development of PMS are considered to be similar to those involved in the development of severe depression (20,21). In rats, it has been observed that a non-selective opioid receptor antagonist was able to alter the time in suspension during forced swimming (22), which improved depressive-like behavior (17,23).…”
Section: Discussionmentioning
confidence: 99%
“…The neurobiological factors involved in the development of PMS are considered to be similar to those involved in the development of severe depression (20,21). In rats, it has been observed that a non-selective opioid receptor antagonist was able to alter the time in suspension during forced swimming (22), which improved depressive-like behavior (17,23).…”
Section: Discussionmentioning
confidence: 99%
“…PMS is characterized by symptoms involving body, mind and behavior that emerge cyclically one to two weeks prior to menstruation (35). These symptoms are relieved soon following the onset of menses.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Most evidence suggest that there is decrease in serotonin and beta-endorphins level during pre-menstrual phase and this might be associated with changes in mood and behavioral symptoms. [1,17,18] Thus during different phases of menstrual cycle neurohormonal changes, stress, and sympathetic activity are interrelated to each other.…”
Section: Discussionmentioning
confidence: 99%